Comparison of radiological imaging techniques for placenta accreta spectrum to optimise feto-maternal outcome by antenatal detection and management plan at a tertiary care centre - Sharma, Deeksha; Kaur, Harpreet; Aggarwal, Muskan; Kaur, Sarvjeet; Kaur, Jyotsimran (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Placenta accreta spectrum remains one of the most dangerous obstetric conditions especially when antenatal suspicion amounts to nil, resulting in severe feto-maternal outcomes. Therefore, accurate and optimal prenatal imaging is mandatory to instigate necessary preparation and strategic management approach. Methods: We conducted a prospective study in our tertiary care centre, Punjab in duration of 18 months enrolling 54 antenatal patients fulfilling the inclusion criteria, reporting to the labour room by non-probability convenient sampling technique. Patients were subjected to radiological imaging (both ultrasonography and MRI) which was then followed by surgery. The data was analysed using suitable statistical software. Results: We observed that patients with previous history of some surgery, be it caesarean section or D and C, pose a greater threat of acquiring placenta accreta syndrome and may tend to cause preterm births. Thus, requisiting antenatal diagnosis with the intent to ameliorate feto-maternal outcomes. Conclusions: MRI has better diagnostic accuracy in terms of sensitivity and overall accuracy than sonography. Although cost and accessibility may limit the use of MRI, both aid in prenatal assessment and multi-disciplinary approach to help improve maternal and fetal outcome.